Adventitious shoot induction from leaf segments in Anthurium andreanum is affected by age of explant, leaf orientation and plant growth regulator - Cardoso, Jean Carlos; Habermann, Gustavo [UNESP] (Korean Soc Horticultural Science, 2014)
Anthurium is one of the main potted plants on the flower market, and micropropagation is the most used technique for clonal and large scale propagation of this species. Calli, adventitious shoots and regenerated plantlets were obtained from leaf segments of Anthurium andraeanum. The influence of genotype, explant orientation, plant growth regulator, and age of donor plants were tested. We obtained regenerated plants in three ('Red One', 'Red Dark', and 'Snow White') out of four different cultivars. The 'White Beauty', however, was considered to be recalcitrant under these conditions. Therefore, the second study was conducted only with this recalcitrant cultivar, and the use of juvenile rather than adult leaf explants enhanced plantlet regeneration at the frequency of 0.3-2.8 plantlets per leaf segment. The use of 1.0 mg center dot L-1 6-benzylaminopurine (BAP) and no addition of 2,4-D in the culture medium resulted in direct plantlet regeneration of Anthurium. Plantlets obtained from 'Red One' and 'White Beauty' were successfully micropropagated and acclimatized. In ex vitro phases, leaf-derived plants of these two genotypes maintained their most important horticultural and ornamental characteristics.
Keywords: direct and indirect organogenesis; ex vitro cultivation; micropropagation; recalcitrant cultivars; true-to-type plants